Targeting mitochondrial reactive oxygen species-mediated oxidative stress attenuates nicotine-induced cardiac remodeling and dysfunction - Anand Ramalingam (Nature Portfolio, 2021)
Abstract Long-term nicotine intake is associated with an increased risk of myocardial damage and dysfunction. However, it remains unclear whether targeting mitochondrial reactive oxygen species (ROS) prevents nicotine-induced cardiac remodeling and dysfunction. This study investigated the effects of mitoTEMPO (a mitochondria-targeted antioxidant), and resveratrol (a sirtuin activator) , on nicotine-induced cardiac remodeling and dysfunction. Sprague–Dawley rats were administered 0.6 mg/kg nicotine daily with 0.7 mg/kg mitoTEMPO, 8 mg/kg resveratrol, or vehicle alone for 28 days. At the end of the study, rat hearts were collected to analyze the cardiac structure, mitochondrial ROS level, oxidative stress, and inflammation markers. A subset of rat hearts was perfused ex vivo to determine the cardiac function and myocardial susceptibility to ischemia–reperfusion injury. Nicotine administration significantly augmented mitochondrial ROS level, cardiomyocyte hypertrophy, fibrosis, and inflammation in rat hearts. Nicotine administration also induced left ventricular dysfunction, which was worsened by ischemia–reperfusion in isolated rat hearts. MitoTEMPO and resveratrol both significantly attenuated the adverse cardiac remodeling induced by nicotine, as well as the aggravation of postischemic ventricular dysfunction. Findings from this study show that targeting mitochondrial ROS with mitoTEMPO or resveratrol partially attenuates nicotine-induced cardiac remodeling and dysfunction.